2021
DOI: 10.1371/journal.ppat.1009565
|View full text |Cite|
|
Sign up to set email alerts
|

Mitigation of endemic GI-tract pathogen-mediated inflammation through development of multimodal treatment regimen and its impact on SIV acquisition in rhesus macaques

Abstract: Here, we assessed the efficacy of a short-course multimodal therapy (enrofloxacin, azithromycin, fenbendazole, and paromomycin) to eliminate common macaque endemic pathogens (EPs) and evaluated its impact on gastrointestinal (GI) microbiota, mucosal integrity, and local and systemic inflammation in sixteen clinically healthy macaques. Treatment combined with expanded practices resulted in successful maintenance of rhesus macaques (RM) free of common EPs, with no evidence of overt microbiota diversity loss or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 43 publications
(66 reference statements)
1
20
0
Order By: Relevance
“…Antibiotics may also negatively affect humans and animals in other ways, due to side effects and microbiome changes [ 8 ]. They have been shown to impact key target cell populations for SIV acquisition and disease progression in the colon, such as Th17+ CD4+ T cells [ 20 ], as well as inducing colitis, which has been shown to have a significant impact on acquisition and disease progression in SIV/SHIV models [ 23 , 27 , 28 ]. Even short courses of antibiotics can cause microbiome perturbations that can persist for weeks to months [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotics may also negatively affect humans and animals in other ways, due to side effects and microbiome changes [ 8 ]. They have been shown to impact key target cell populations for SIV acquisition and disease progression in the colon, such as Th17+ CD4+ T cells [ 20 ], as well as inducing colitis, which has been shown to have a significant impact on acquisition and disease progression in SIV/SHIV models [ 23 , 27 , 28 ]. Even short courses of antibiotics can cause microbiome perturbations that can persist for weeks to months [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobials should not be used based on perceived risk, as is the case when prophylactic antibiotics are used in SIV infected macaques undergoing clean, minimally invasive surgeries. It is essential to follow evidence-based practices, as were performed in this study, to ensure antimicrobial use has clear benefits, such as those demonstrated with elimination of endemic gastrointestinal pathogens in macaques [ 27 ]. Finally, given the similarities in outcomes between SIV infected macaques and HIV infected patients, it is likely that where similar conditions exist (highly trained surgeons, clean surgeries, minimally invasive procedures, and the ability to achieve good aseptic technique), prophylactic antibiotics are also likely unnecessary in HIV patients.…”
Section: Discussionmentioning
confidence: 99%
“…In humans and animals, fluoroquinolone treatment is a known risk factor for carrying methicillin-resistant Staphylococcus aureus (MRSA) [ 9 ]. There is increasing emphasis on the need to use the ‘precautionary principle’ when assessing AMR risks, and it is highly plausible that the treatment proposed in Bochart et al [ 1 ] similarly drives MRSA selection in macaques. The multi-antimicrobial regimen described was implemented many years ago, albeit without the use of azithromycin, at the National Cancer Institute [ 11 ].…”
Section: Development Of Antimicrobial Resistance and Risk To Human He...mentioning
confidence: 99%
“…Finally, if this approach is used, it must be reported in the literature in the methods section of papers to promote research reproducibility. Given the significant impact that pre-study antimicrobials can have on the microbiome of asymptomatic macaques [ 22 ] and the observations associated with mucosal inflammation [ 1 ], reporting such treatments must be a requirement in the materials and methods of all publications, regardless of the aims of the research.…”
Section: Concerns About Translatability and Research Reproducibilitymentioning
confidence: 99%
See 1 more Smart Citation